The Effect of Individual Innovativeness Characteristics on Attitudes Towards Evidence Based Practices in X and Y Generation Nurses - Ayşegül Yayla; Ayşegül Sarıoglu Kemer (Association of Nurse Managers, 2020)
INTRODUCTION: The present study aimed to determine the effect of individual innovativeness characteristics on evidence-based practice attitudes of X and Y generation nurses. METHODS: The descriptive and correlational study population comprised of 560 nurses. The study sample consisted of 338 nurses who agreed to participate in the study and whose data were available to use. Data were collected using a Personal Information Form, Attitude Towards Evidence-Based Nursing Questionnaire and Individual Innovativeness Scale and expressed with numbers, percentage and mean, independent groups t-test, Pearson correlations, linear regression and Cronbach's alpha analyses. RESULTS: In the present study, Individual Innovativeness Scale mean scores of the Y generation nurses were 67.54+-7.58 while it was 62.12+-8.01 for the X generation. Attitude Towards Evidence-Based Nursing Questionnaire mean scores of X generation nurses was 52.08+-8.13 while it was 58.13+-9.20 for the Y generation. Individual innovation attitudes towards evidence-based nursing were 24% determinant in the X generation nurses and 49% in the Y generation. DISCUSSION AND CONCLUSION: The findings showed that the Y generation nurses were more innovative and had more positive evidence-based practice attitudes. Differences between the generations should be taken into consideration to increase nurses' individual innovation characteristics and their evidence-based attitudes.